Effects of Using Fermented Moringa (Moringa oleifera) Leaf Meal and Yellow Corn in the Diets on the Performances and Income Over Feed Cost of the Broiler Chickens - Zulfan Zulfan; Zulfikar Zulfikar; Herawati Latif; Allaily Allaily; Taufik Nazarullah; Rhaudatul Shaleha (Agricultural Faculty, 2021)
ABSTRAK. Recently, exploring unconventional feedstuffs were not merely interested at the point of lower cost, but also natural sources and supporting bird health have been noticing on the critical assessments by poultry nutritionists to serve well broiler meat. This study aimed to examine the effect of including fermented moringa leaf meal (fMOL) + yellow corn (yC) to substitute fractionally commercial diet (CD) on the performances and Income over Feed Cost (IOFC) of the broiler chickens. The study was done in the Field Laboratory of Animal Husbandry, Animal Husbandry Department, Syiah Kuala University from August 4 until September 15, 2020. The study used 100 broiler chicks strain CP 707, unsex. This study was set up into Block Randomized Design (BRD) consisting of 4 treatments and 5 blocks. The treatments were MC0 = 100% CD, MC1= 95% CD + 2,5% fMOL + 2,5% yC, MC2= 90% CDR + 5% fMOL + 5% yC, and MC3= 85% CD + 7,5% fMOL + 7,5% yC. The results of studies showed that including fMOL + yC to substitute partly commercial diet significantly (P0.05) reduced final body weight (FBW) and increased feed conversion ratio (FCR) of the broilers. Feed consumption statistically was not significantly affected but tended to reduce. Using fMOL + yC reduced feed cost but revenue and IOFC also declined.(Pengaruh penggunaan campuran daun kelor dan jagung terhadap performan dan IOFC ayam broiler) ABSTRACT. Tujuan penelitian ini adalah untuk melihat pengaruh penggunaan tepung daun kelor fermentasi (TKF) ditambah dengan jagung kuning (JK) sebagai pengganti sebagian ransum komersil (RK) terhadap performan ayam broiler. Penelitian ini dilakukan di Laboratorium Lapangan Peternakan, Fakultas Pertanian Universitas Syiah Kuala, Banda Aceh. Materi yang digunakan adalah 100 ekor DOC ayam broiler strain CP 707. Ransum perlakuan adalah MC0= RK 100%, MC1= 95% RK + 2,5% TKF + 2,5% JK, MC2= 90% RK + 5% TKF + 5% JK, dan MC3= 85% RK + 7,5% TKF + 7,5% JK. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK) terdiri dari 4 perlakuan dan 5 kelompok. Pengelompokan didasarkan pada berat badan ayam pada awal minggu ketiga. Parameter yang diamati meliputi berat badan akhir, konsumsi dan konversi ransum, dan Income Over Feed and Cost (IOFC), Hasil penelitian memperlihatkan bahwa penggunaan TKF + JK sebagai substitusi sebagian ransum komersil nyata (P0,05) menurunkan berat badan akhir dan meningkatkan konversi ransum. Konsumsi ransum tidak nyata berpengaruh, namun cenderung menurun. Pengunaan daun kelor menurunkan biaya ransum, dan IOFC.